Pengaruh Variasi Konsentrasi Asam pada Pembuatan Bioetanol dari Buah Kumbi (Voacanga foetida (Bl.) ROLFE) melalui Proses Hidrolisis - Sulwiyatul Kamariyah Sani (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Currently, the availability of petroleum and natural gas as non-renewable energy sources is steadily decreasing. One alternative energy source that can be developed for the future is bioethanol, as it is renewable and environmentally friendly. The kumbi fruit (Voacanga foetida (Bl.) ROLFE) is a potential raw material for bioethanol production due to its cellulose content, which can be converted into bioethanol. The objective of this study was to investigate the effect of acid concentration on the hydrolysis process in the production of bioethanol from kumbi fruit. In this study, hydrolysis was carried out using HCl at concentrations of 1%, 2%, 3%, 4%, and 5% (v/v) at 70°C for 90 minutes. To determine the reducing sugar content produced, the hydrolysate was analyzed using UV-Vis spectrophotometry. The hydrolysate was then fermented using baker's yeast containing Saccharomyces cerevisiae for 72 hours. The fermentation product was distilled at 78°C, and the obtained bioethanol was analyzed using GC-MS. The results showed that the highest reducing sugar concentration was obtained at 2% acid concentration, amounting to 7.18 g/L, while the highest crude bioethanol yield was 47.64%, achieved at 4% acid concentration with a reducing sugar content of 1.04 g/L.